EVALUATION OF COAL DETERMINATION AS TAXABLE GOODS AND ITS EFFECT ON VAT TAX PLANNING & FINANCIAL STRATEGY TO OPTIMIZE FINANCIAL PERFORMANCE OF PT ABC - Tomi Yulianto; Subiakto Sukarno (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
PT ABC, a coal mining company, is preparing to undertake major infrastructure projects specifically the construction of Train Loading Systems (TLS) 6 and 7 to enhance logistics capacity and operational efficiency in line with its long-term goals. However, implementing both projects simultaneously require significant funding, potentially straining the company’s liquidity. To ensure financial sustainability, an integrated strategy is necessary during the investment phase. This research applies both quantitative and qualitative methods to develop a financial strategy that supports project execution without disrupting core operations. The strategy focuses on optimizing financing structures and tax planning, particularly through the use of input VAT to improve cash flow. Two alternative financing schemes were analysed: Alternative I, combining tax optimization with debt securities; and Alternative II, combining tax planning with bank financing. Simulation results show that Alternative II offers better financial outcomes. It provides greater cost efficiency and less strain on cash flow during construction. Under this approach, interest expenses are deferred until commercial operations begin, and Interest During Construction (IDC) is capitalized into the asset and loan balance. This results in a structured repayment schedule that lowers future interest burdens. Conversely, Alternative I requires fixed quarterly coupon payments from the outset, placing continuous pressure on cash flow and the income statement throughout the construction period. Given these considerations, Alternative II is recommended as the more financially sustainable option, allowing PT ABC to proceed with its infrastructure projects while maintaining healthy operational liquidity.